2007
DOI: 10.1161/01.str.0000255784.27298.23
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Immune-Based Therapy for Stroke Induces Neuroprotection and Supports Neurogenesis

Abstract: Abstract-The ability of the central nervous system to cope with stressful conditions was shown to be dependent on proper T-cell-mediated immune response. Because the therapeutic window for neuroprotection after acute insults such as stroke is relatively narrow, we searched for a procedure that would allow the relevant T cells to be recruited rapidly. Permanent middle cerebral artery occlusion was induced in adult rats. To facilitate a rapid poststroke T cell activity, rats were treated with poly-YE using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…The acquirement of a dendritic cell phenotype may indicate a role for adaptive immunity in ALS, as these cells are antigen presenting cells required for efficacious activation of naive and memory B and T cell (Banchereau and Steinman, 1998). Interestingly, the presence of microglia-expressing molecules associated with antigen presentation have been associated with neuroprotective effects in various models of CNS injury (Byram et al, 2004;Shaked et al, 2004;Ziv et al, 2007). However, the importance of this microglial cell phenotype in ALS remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The acquirement of a dendritic cell phenotype may indicate a role for adaptive immunity in ALS, as these cells are antigen presenting cells required for efficacious activation of naive and memory B and T cell (Banchereau and Steinman, 1998). Interestingly, the presence of microglia-expressing molecules associated with antigen presentation have been associated with neuroprotective effects in various models of CNS injury (Byram et al, 2004;Shaked et al, 2004;Ziv et al, 2007). However, the importance of this microglial cell phenotype in ALS remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although basic differences between the postischemic brain and the postinjury spinal cord might preclude the translation of this approach to stroke, the common themes of a limited therapeutic window and coopting immune cells to promote a more neurogenic microenvironment beckon a closer look. Indeed, studies by these same authors 99 as well as others 36 have revealed how modulation and/or suppression of inflammation after stroke can promote neuroprotection and neurogenesis. This fascinating cross-talk between neural and immune cells reveals additional therapeutic opportunities for attenuating postischemic inflammatory damage and providing a more hospitable environment for the persistence of both endogenous and transplanted NPCs.…”
Section: Stem Cell-induced Immunomodulationmentioning
confidence: 94%
“…In the same way, Poli-Y immunomodulator has also shown an increment in cortical and hippocampal neurogenesis, as well as reduction of neural loss [88].…”
Section: Immune Response As a Neurorestorative Mechanismmentioning
confidence: 84%
“…"fter subjecting rats to experimental stroke, those treated with poly-YE presented diminished infarct size and neurological deicit [88].…”
Section: Modulation Of Immune Response As a Therapy For Strokementioning
confidence: 99%